If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3tgx + 4 = tgx + 4 Reorder the terms: 4 + 3gtx = tgx + 4 Reorder the terms: 4 + 3gtx = 4 + gtx Add '-4' to each side of the equation. 4 + -4 + 3gtx = 4 + -4 + gtx Combine like terms: 4 + -4 = 0 0 + 3gtx = 4 + -4 + gtx 3gtx = 4 + -4 + gtx Combine like terms: 4 + -4 = 0 3gtx = 0 + gtx 3gtx = gtx Solving 3gtx = gtx Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1gtx' to each side of the equation. 3gtx + -1gtx = gtx + -1gtx Combine like terms: 3gtx + -1gtx = 2gtx 2gtx = gtx + -1gtx Combine like terms: gtx + -1gtx = 0 2gtx = 0 Divide each side by '2'. gtx = 0 Simplifying gtx = 0 The solution to this equation could not be determined.
| 18/x-3=6 | | 2x^2+6=166 | | 15x^2-2=123 | | 2w=10w-32 | | 7x-11=5x-15 | | 90=-6+2(-4x+10) | | 0=2x^2-6x+24 | | V+8=-3 | | h(t)=-5t^2+80t+3 | | 7x+9=-3y | | 5x^2-2=123 | | 15-10*4= | | 3x+7+3y-1=180 | | ×/4=3.6 | | -2b+3b=19 | | 3(2x+5)=8x+3 | | 0.044x=200 | | X+8x+90=180 | | 25p-5=5 | | 2(x+1)+5=-7(x+1)-13 | | 4/=3.6 | | 45=9(5c+12) | | 3m^2=30+13m | | 37=130/x | | 28-9x=3 | | -7f+6=166+3f | | 2x-(13)=3 | | 2/3x^2-1/3=0 | | z=2z-70 | | (4x)(-3xy^2)= | | (4x+9)-(x+9)=33 | | -(12-x)=4 |